(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
Artificial Intelligence is no longer something distant and futuristic. It is already in our classrooms, on our phones, and in the tools that students use every day. In Uzbekistan, where English is becoming a key to global opportunities, AI can transform how young people learn, practice, and communicate in English. From mobile apps that correct grammar to virtual tutors that speak English 24/7, technology is reshaping the language classroom into a dynamic, interactive space.